Gender Differences in Lower Extremity Stiffness during a Single-Leg Landing Motion in Badminton - Yanan Zhang; Zhe Hu; Bairan Li; Xuan Qiu; Ming Li; Xiangwei Meng; Sukwon Kim; Youngsuk Kim (Bioengineering, 2023)
In general, at the same level of exercise, female athletes are three to six times more likely to injure an anterior cruciate ligament (ACL) than male athletes. Female athletes also had higher rates of ACL injury than males in a single-leg landing task after a backcourt backhand side overhead stroke in badminton. In many previous studies, stiffness of the musculoskeletal system in the lower limbs has been reported as a potential factor contributing to differences in ACL injury rates between genders. The purpose of this study was to describe the differences between genders in leg and knee stiffness in male and female athletes during a single-leg landing action after the backhand side overhead shot in the backcourt. Eight male athletes and eight female athletes participated in this test. Leg stiffness and knee stiffness were calculated separately for male and female athletes during the landing phase. The results showed that both absolute and normalized leg stiffness were lower in female athletes than in male athletes (p < 0.05). And both absolute and normalized knee stiffness were also lower than male athletes (p < 0.05). The low leg stiffness and knee stiffness demonstrated by females in this single-leg drop task compared to male athletes may indicate that females have lower dynamic leg stability than males during the drop, which may lead to hypermobility of the knee joint and may put females at a higher risk of injury in this high-risk maneuver for non-contact cruciate ligament injuries.